Security and Compliance Issues in Cloud-Based Deployments of Content and Workflow Management Systems - Ravi Kiran Kanneganti (Eastasouth Institute, 2024)
The spread of cloud-based content and workflow management systems has increased boisterously within industries, and usage has subjected organizations to severe security and compliance threats. This paper discusses these risks based on a process of systematic analysis of literature on twenty peer-reviewed sources. We are able to categorize five types of threats, analyze five hypothetical compliance models and provide a quantitative security assurance model based on weighted scoring. Conclusions indicate that data breaches and identity management successes and failures occur in content and workflow environments and can explain about 50% of reported incidents of cloud security. The three frameworks of compliance vary in terms of coverage, ease of implementation and integration of workflow. The article suggests a layered security architecture and quantitative assurance metrics to enable decision clouds to select cloud services and design policies based on that selection. Companies with coordinated compliance strategies have significantly low numbers of violations, and improved overall security status.